CONCEPTUAL UNDERSTANDING OF PRODUCT BRANDING TO EXPAND THE MARKET FOR THE GROUP OF MSMEs AMANAH IN PACAREJO SEMANU GUNUNGKIDUL - Indria Desy Rachmawati; Ardi Ariyanto; Syahida Norviana; Entus Nuryana Ahmad (Jurnal Pengabdian Masyarakat Sabangka, 2026)
This community service activity aimed to provide the Amanah MSME group with an understanding of the importance of branding for products in order to enhance competitiveness and expand market reach. Appropriate branding enables MSMEs to create a strong product identity that aligns with market characteristics, which is expected to increase sales and improve economic welfare. The methods used in this activity included training sessions and practical mentoring for the Amanah MSME group. The training materials covered basic concepts of branding, simple market analysis using mobile phones, and hands-on practice in determining suitable branding strategies for MSME products. After the training, participants gained a broader understanding of the market and were able to independently develop branding for their products. The results indicate that this activity effectively increased participants’ knowledge and skills in product branding, thereby supporting the development of more competitive and sustainable MSMEs.